Beyond Digitalization: AI-Driven Administrative Management and Its Impact on School Quality Improvement - Maskanah Maskanah; Adiyono Adiyono; Nur Muhammad; Ali Said Al-Matari; Iro Waziroh (Institut Agama Islam Negeri Palangka Raya, 2026)
The fast-disrupting entry of artificial intelligence (AI) into educational administration has warranted the need to decipher how digital transformation works beyond passing technical efficiencies; indeed, digital transformation creates havoc at the heart of school quality improvements. Existing literature mainly focuses on technology adoption and results pertaining to performance outcomes, while relatively lesser emphasis is given to the introduction of organizational and professional changes that accompany AI-borne administrative practices. This study aims to analyze the re-engineering of administrative workflows, decision-making, and professional roles in school management as a function of AI-supported administrative management. This research took a qualitative case study approach to provide a deeper understanding of AI-enabled administrative change in a school context. Data were gathered through semi-structured interviews with school leaders and administrative staff, non-participant observation of administrative processes, and secondary document analysis. The data were thematically analyzed for recurring patterns of efficiency, transparency, and transformation of professional practice. The findings suggest that AI-based administration improves the means of procedure efficiency and enhances the accuracy and transparency of data, and refashions administrative roles to function more in analytical and coordinative aspects rather than in routine clerical functions. Most significantly, the study shows that AI in reality acts as an enabling infrastructure restructuring administrative logic and organizational practices, but does not simply automate them. The results depict the importance of adopting a process perspective of AI integration, which can inform better and more context-specific educational management policies.